Atrial Fibrillation and Heart Failure Parallels: Lessons for Atrial Fibrillation Prevention - McManus, David D. (2011)
Heart failure (HF) and atrial fibrillation (AF) are two of the most common cardiovascular diseases encountered in clinical practice, and the prevalence of these diseases continues to grow world-wide with the aging of the global population. While recognizing that AF is a heterogeneous disorder, we submit that the parallels between AF and HF may arise because many cases of AF and HF result from the cumulative exposure of the atria and ventricles to a common set of systemic cardiovascular risk factors. Over time, exposure to risk factors promotes development of atrial and ventricular structural and functional abnormalities via activation of several biological pathways in concert: up-regulation of neurohormonal signaling cascades, release of inflammatory mediators, programmed cell death and fibrosis. Cardiac structural remodeling occurs in concert with electrophysiologic remodeling, both of which contribute to atrial and ventricular rhythm disturbances, including AF. AF and HF, instead of representing distinct disease processes, often represent different endpoints along a disease continuum. By reviewing some of the mechanistic parallels between AF and HF, we hope to emphasize the connection between established cardiovascular risk factors, cardiac remodeling and AF, with a view to promoting strategies for AF prevention.